Peran Strategis Kelompok Tani dalam Implementasi Teknologi Budidaya Padi di Kabupaten Toraja - Elviani Randanan; Mahmud, Musdalipa; Ibrahim, Helda; Nursaman, Herman (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
The use of technology in rice farming can significantly increase production, reduce management time, expand cultivated land, and improve product quality to meet consumer standards. When rice production meets market demand, the selling price becomes higher, thus increasing farmers’ income and welfare. The presence of farmer groups plays a vital role as a learning forum for gaining knowledge, implementing agricultural technology, and facilitating access to agricultural tools and machinery. This enables farmers to apply technology effectively, improve work efficiency, and address challenges in rice farming. Considering the great potential of this region for rice cultivation, supported by growing local food demand and the national food security program, technology implementation becomes essential. This study employed the Likert scale method to measure farmers’ attitudes, opinions, and perceptions, with samples collected through purposive sampling. The findings show that the role of farmer groups in implementing rice farming technology in the Misa Kada (Advanced) group reached 74.91%, while the Ta’pan Kila’ (Beginner) group reached 66.07%. This indicates that farmer groups have contributed effectively, though some activities remain suboptimal. Strengthening learning class programs is the most strategic effort to enhance farmers’ understanding of agricultural technology, improve productivity, and maintain Tana Toraja’s cultural values.